Bases moleculares da interação de lectinas da subtribo Diocleinae com glicoconjugados - Bomfim, Liezelotte Rezende (2005)
Title: Molecular Basis of The Glycoconjugate Specificity of Lectins From SubTribe Diocleinae. Background: Proteins exhibiting non-catalytic binding sites towards carbohydrates form a class of very heterogeneous molecules commonly designed lectins. These proteins have been used as study-model molecules to understand the molecular basis of protein-carbohydrate interactions. Seeds of the subtribe Diocleinae are a rich source of lectins whose primary specificity is addressed to glucose/mannose monosaccharides. However, despite this and many other structural features shared by Diocleinae lectins they display difterent recognition to glycoconjugates like N-acetyllactosamine and oligomannoside types. The present work aimed to determine the molecular basis of the oligosaccharide specificity of the Diocleinae lectins towards glycoproteins and purified glycopeptides on a comparative basis to other legume lectins. The experimental strategy included analysis of the kinetic interaction (and inhibition) of soluble lectins with immobilized glycoproteins based on Surface Plasmon Resonance (RPS-BiaCore Technology); Aftinity of immobilized lectins to soluble radio-Iabelled oligosaccharides and glycopeptides and autoradiography analysis of the fractionated structures upon lectin aftinity column. Material and Methods: The seed lectins from Canavalia brasiliensis, C. maritima, C. bonariensis, Cratylia floribunda, Dioclea grandiflora, D. virgata and D. violacea, D. guianensis were purified by aftinity chromatography as previously described in the literature. The purified lectins were assayed for kinetic interaction analysis with immobilized glycoproteins exhibiting distinct oligosaccharide structures of N-acetyllactosamine and oligomannoside types and inhibition of the interaction by monosaccharides. Further, the glycoconjugate specificity of the lectins was investigated by aftinity chromatography of radio-Iabeled glycopeptides and oligosaccharides of difterent origins and well-defined structures on lectin-Sepharose 4B columns. The ability of these lectins to fractionate complex mixtures of closely related oligomannoside structures was determined by autoradiography analysis of the chromatography fractions eluted from the lectin columns. Results: The lectins showed ability to interact with glycoproteins exhibiting both Nacetyllactosamine and oligomannoside type glycans. The kinetic interaction varied considerably among the proteins under similar experimental conditions. The monosaccharides glucose and mannose were eftective to diminish lectinglycoprotein interactions at concentrations as lower as 25 mM. Upon affinity chromatography, the lectins showed interaction with N-acetyllactosamine type asparagin-glycopeptides but the recognition was limited to biantennary structures. Larger structures possessing three or more antennas were completely devoid of interaction. The lectins seem to bind and discriminate biantennary glyeopeptides/oligosaeeharides of N-aeetyllaetosamine type but failed to reeognize their eounterparts with multi-antennas. They were able to diseriminate native and asialo forms of the biantennary N-aeety//aetosamiane glyeopeptide purified from human serum transferrin. The affinity was maxima when the glycopeptide was previously digested to exhibit galactose and further N-acetylglucosamine in its non-reducing end. Its related oligosaccharide, devoid of sialic acid was recognized by D. virgata but not by D. violacea. Glycopeptides from Orosomucoide, containing mainly a mixture of bi- tri- and tetra-antennary glycopeptides were not recognized by the lectins. Interaction with oligomannosides was drastically differentiated. Affinity was proven to be stronger proportionally to the presence and number of mannose residues a-(1 -> 2) linked in the outer of structures. Thus Man9 was strongly recognized while Man5 was poorly. Of great relevance was that the lectins seems to be able to separate some of the oligomanoside structures within a complex mixture and it is not ruled out that Man8 or Man7 isomers could be fractionated under well-determined experimental conditions. Conclusions: Requisites for bind glycopeptides or oligosaccharides in the carbohydrate-binding site of the lectins include the presence of the monosaccharide inhibitor of the lectin activity and the accessibility for it, but does not define the affinity of the lectins for glycoconjugates. According to the results, the lectins may recognize internal mannose residues in the N-acetyllaetosamine type oligosaeeharides and the affinity increases as much exposed as the trimannoside core is presented. Regarding the recognition of oligomannosides the rule is opposite. The presence of Mannose residues a-(1->2) linked in the outer of structures seems to play a key role in the affinity. However the presence of these residues as occurs in Man6 and mainly in Man7 up to Man9 suggests that the monosaccharide that arbors the lectins should not be the same that plays this role in the interaction with N-acetyllactosamine type. Comparing this performance with that of other mannose-binding legume as Parkia platycephala and non-Iegume leetins it makes clear that the affinity to binding oligosaeeharides is not defined solely by the carbohydrate-binding but instead it, the vicinity of the monosaccharide pocket should possesses structural characteristies to differentiate each lectin-glycoconjugate complex that is supported by the concept of extended binding-site and epitope recognition. Divergences in affinity among Diocleinae lectins ought reflect this hypothesis and thus explain at least in part their differential performance in binding the same structure. This work was supported by grants from CAPES/COFECUB, CNPq, FUNCAPCe and International Foundation for Science.